Reactions for actions? Trust in protective behaviors and safeguarding measures in the early phase of the Covid-19 pandemic in Sweden - Andersson, Elin M.; Norberg, Margareta (Preventive medicine reports, 2023)
To minimize the spread of Covid-19, changing every-day behavior has been key. Trust in the effectiveness of individual protective measures (response efficacy) and confidence in collective safeguarding measures (strategy efficacy), offers an incitement for acting adequately. Efficacy beliefs of protective measures might be especially relevant to study in the Swedish context, since Sweden, in contrast to countries facing hard lock-downs, launched safeguarding measures based on individual responsibility and voluntary actions. We aimed to assess associations between on the one hand, response efficacy and strategy efficacy, and on the other hand, propensity for behavior change and support of protective measures. Furthermore, to assess associations between the efficacy beliefs and comprehension of and confidence in information about the virus, prosocial beliefs and worry of Covid-19. Reactions were assessed in a Swedish sample close in time to experiences via the SEMA3 app from March 25th to May 17th 2020. Study participants had replied to questions on strategy efficacy (n = 175) or response efficacy (n = 157) and 146 participants had replied to both. High response efficacy was associated with propensity for behavior change, support of protective measures and confidence in Covid-19 information. Low strategy efficacy was associated with lower comprehension of and confidence in information about Covid-19. The results suggest that strengthening efficacy beliefs can be a way to promote protective behaviors. Furthermore, the result underscores the importance of information being easy to understand and trustworthy. Finding ways to increase public understanding of the effectiveness of protective measures, including vaccination, seems crucial in pandemic times.